Identification of stress transfer in asphalt mixtures based on a reconstruction analysis of the simplified coarse aggregate skeleton. (17th March 2023) - Cai, Xu; Tang, Haizhu; Yang, Xiucheng; Nie, Guihai; Liu, Xiaoyu; Wu, Kuanghuai; Huang, Wenke
Highlights: A simplified skeleton method for coarse aggregates analysis of asphalt mixtures was proposed. The stress transfer paths and load transfer efficiencies of three typical gradations were studied. Eff skeleton reflected the load transfer efficiency of the coarse aggregate skeleton under no-load conditions. The DisP value reflected the load transfer efficiency of the coarse aggregate skeleton under a specific load. Abstract: Studies on asphalt mixture skeletons have primarily focused on the statistical skeleton morphology while neglecting internal stress transfer. This study therefore proposed a simplified reconstruction-based coarse aggregate skeleton method for analyzing asphalt mixes using the force chain concept from granular matter mechanics. The stress transfer paths and load transfer efficiencies were investigated for three typical aggregate gradations (AC-13, SMA-13, and OGFC-13) and an analysis of their correlation with uniaxial penetration test results was performed. The AC-13 mixture exhibited the largest uniaxial penetration strength (3.30 kN on average) at the lowest failure displacement (4.1 mm on average). As the characteristics of the simplified skeleton were shown to be related to the number of contact points provided between large aggregate particles, the force chain morphology was closely linked to the mixture gradation. The ratio of strong to weak force chains in the AC-13 mixture was approximately 0.77, whereas those of the SMA-13 and OGFC-13 mixtures were significantly different at 0.90 and 1.13, respectively. The transfer efficiencies of the AC-13, SMA-13, and OGFC-13 specimen skeletons considering morphology alone (i.e., under the no-load condition) were 20.94 %, 62.34 %, and 73.57 %, respectively. However, the correlation between the load transfer efficiency of the coarse aggregate skeleton under a specific load and the observed penetration strength reached 0.9. Thus, the simplified skeleton analysis method proposed herein was shown to satisfactorily retain the skeletal characteristics of the mixes.